Cellular Viability of Partial Heart Transplant Grafts in Cold Storage - Kwon, Jennie H.; Hill, Morgan Ashley; Gerry, Brielle; Morningstar, Jordan; Kavarana, Minoo N.; Nadig, Satish N.; Rajab, Taufiek Konrad (Frontiers in Surgery, 2021)
Congenital heart defects are the most common types of birth defects in humans. Children with congenital heart defects frequently require heart valve replacement with an implant. Unfortunately, conventional heart valve implants do not grow. Therefore, these children are committed to serial re-operations for successively larger implant exchanges. Partial heart transplantation is a new and innovative approach to deliver growing heart valve implants. However, the transplant biology of partial heart transplant grafts remains unexplored. This is a critical barrier for clinical translation. Therefore, we investigated the cellular viability of partial heart transplants in cold storage. Histology and immunohistochemistry revealed no morphological differences in heart valves after 6, 24, or 48 h of cold storage. Moreover, immunohistochemistry showed that the marker for apoptosis activated caspase 3 and the marker for cell division Ki67 remained unchanged after 48 h of cold storage. Finally, quantification of fluorescing resorufin showed no statistically significant decrease in cellular metabolic activity in heart valves after 48 h of cold storage. We conclude that partial heart transplants remain viable after 48 h of cold storage. These findings represent the first step toward translating partial heart transplantation from the bench to the bedside because they have direct clinical implications for the procurement logistics of this new type of transplant.